Association between MCT1 T1470A polymorphism and climbing status in Polish and Japanese climbers - Mika Saito; Michał Ginszt; Myosotis Massidda; Paweł Cięszczyk; Takanobu Okamoto; Piotr Majcher; Koichi Nakazato; Naoki Kikuchi (Termedia Publishing House, 2020)
Sport climbing will become an official event at the 2020 Tokyo Olympics; it is a popular wilderness sport among athletes and amateurs. Our previous study suggested that the T1470A polymorphism (rs1049434) of the monocarboxylate transporter 1 (MCT1) gene is associated with athletic performance and physiological phenotypes. The purpose of this study was to investigate the frequency of MCT1 T1470A polymorphism in Polish and Japanese climbers using a case-control study. Our sample consisted of 226 climbers (Japanese: n = 100, 64 male and 36 female; Polish: n = 126, 97 male and 29 female) and 1028 non-athletic controls (Japanese, n = 407; Polish = 621) who were genotyped for the MCT1 T1470A polymorphism (rs1049434) using the TaqMan SNP genotyping assay or restriction enzyme. The frequency of the TT genotype and T allele was significantly higher in climbers than in controls among the Polish subjects (genotype: p = 0.030, allele: p = 0.010); however, there were no significant differences in the genotype and allelic frequencies between the Japanese climbers and controls (genotype: p = 0.968; allele: p = 0.803). Our results suggested that the frequency of the T allele (TT+TA genotype) in the MCT1 T1470A polymorphism is over-represented in Polish climbers but not in Japanese climbers. In addition, the frequency of the T allele and TT genotype in Polish lead climbers is higher than that in controls.